SISTEM PAKAR DIAGNOSA PENYAKIT REFRAKSI MENGGUNAKAN METODE FORWARD CHAINING BERBASIS WEB - Edha Jenny Cahyani; Sandy Kosasi (P3M STMIK Profesional Makassar, 2022)
Refractive diseases often occur in the community. Many people are not aware of the symptoms, some are aware that they are reluctant to consult directly with a doctor for reason that they are afraid of spending a large amount of money just to diagnose refractive disease. Based on some these problems, system that can adopt ability of an expert is an expert system. With this expert system, it can be a solution for community in diagnosing refractive diseases. Expert system diagnose refractive disease was built using the forward chaining method. Software designed using prototype method by using Design Science Research method. Software testing uses black-box testing method, program code units with boundary value testing techniques. Results of this software design in the form of software that’s named